Study on the Issues of Foreign-related Legal Professionals’ Participation in Ecological and Environmental Legislation - Jing , Zhen; Jia, Gan (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
In the context of deepening globalization and the internationalization of environmental governance, ecological and environmental legislation has evolved into a complex transnational and interdisciplinary system. This article examines the necessity of involving foreign-related legal professionals in the process of ecological and environmental lawmaking. It analyzes the key practical challenges associated with their participation in domestic legislative activities. The purpose of the study is to identify the role and potential of such professionals in adapting international environmental legal norms to national legal systems and ensuring coherence between domestic legislation and international obligations. The research employs methods of systematic analysis, comparative legal analysis, and formal legal interpretation. The findings demonstrate that the active participation of foreign-related legal professionals contributes to improving the quality of environmental legislation, enhancing international legal compatibility, and strengthening mechanisms for transboundary environmental regulation. The article concludes that it is essential to improve talent cultivation systems, expand institutionalized channels for participation in legislative processes, and establish sustainable mechanisms for integrating international environmental standards into national legal frameworks to promote the internationalization of the rule of law in environmental governance.